Capturing the implications of services trade liberalization - Robinson, Sherman; Wang, Zhi; Martin, Will (Informa UK Limited, 2002)
This paper evaluates the impact of service sector trade liberalization on the world economy by a ten-region, eleven-sector CGE model with import embodied technology transfer from developed countries to developing countries. Simulation results show that service sector trade liberalization not only directly affects world service production and trade, but also has significant implications for other sectors in the economy. The major channel of the impact is through inter-industry input-output relations and TFP growth induced from services imported by developing countries from developed countries, which may be embodied with new information and advanced technology." -- Abstract